Fixed Retainer with Artificial Teeth in Patients with Cleft Lip and Palate: Possibility as an Adhesive Bridge - SUSAMI, Takafumi; MARUOKA, Ryo; UCHINO, Natsuko; UGA, Rin; HOSHI, Kazuto; OHKUBO, Kazumi; OKAYASU, Mari (Journal of Japanese Cleft Palate Association, 2020)
After orthodontic treatment in patients with cleft lip and palate, a space is sometimes left in the dentition. For closure of this space, the use of a fixed retainer with artificial teeth has been preferred in recent times in our hospital. This study examined the use of this appliance in our hospital. The subjects included 308 patients with cleft lip and palate who underwent active orthodontic treatment from 1993 to 2019. Records, including oral photographs, radiographs, and dental models, were used for the clinical examination. We retrospectively investigated the records for the following: cleft type, observation period, existence of residual dental space and application of fixed retainer with artificial teeth at the start of retention, change of appliance to and from fixed retainer with artificial teeth, the site and number of artificial teeth, lingual wire fixation range, simultaneous use of removable retainer, breakdown （functional survival rate by Kaplan-Meier method）, and occurrence of dental caries. Cleft types of the 308 patients were as follows: 72 unilateral cleft lip and alveolus, 9 bilateral cleft lip and alveolus, 142 unilateral cleft lip and palate, and 85 bilateral cleft lip and palate. The mean observation period was 4 years and 1 month. At the alveolar cleft site, residual space was observed in 65 patients （21.1％） and this appliance was placed in 23 patients （35.4％）. During the retention period, the appliance was changed from the removable retainer with artificial teeth to this appliance in five patients, resulting in this appliance being used in 28 patients （43.1％）. This appliance was changed to prosthetic appliances in three patients. The artificial teeth were aligned at the position of the lateral incisors in 17 patients （60.7％） and the central incisors in 9 patients （32.1％）. Three to 8 teeth were used to fix the appliance. Twenty-six of 28 patients （92.9％） used the removable retainer simultaneously. The functional survival rate was 72.2％ at 13 years and 6 months. Five patients （17.9％） had dental caries. This appliance is useful for the retention of anterior teeth without shaving of the adjacent teeth and can be used for the long term, like an adhesive bridge. Appropriate maintenance with a regular follow-up of four to six months was considered necessary for long-term use.